2016
DOI: 10.1073/pnas.1521093113
|View full text |Cite
|
Sign up to set email alerts
|

Drift in ocean currents impacts intergenerational microbial exposure to temperature

Abstract: Microbes are the foundation of marine ecosystems [Falkowski PG, Fenchel T, Delong EF (2008) Science 320(5879): [1034][1035][1036][1037][1038][1039]. Until now, the analytical framework for understanding the implications of ocean warming on microbes has not considered thermal exposure during transport in dynamic seascapes, implying that our current view of change for these critical organisms may be inaccurate. Here we show that upper-ocean microbes experience along-trajectory temperature variability up to 10°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 48 publications
3
80
0
Order By: Relevance
“…Equatorward-flowing currents, like the Falkland Current and Canary Current, have negative differential. These global patterns are also qualitatively similar to those for temperature offsets for drift of planktic foraminifera presented by van Sebille et al [26] and the inter-generational temperature ranges due to drift experienced by microbes presented by Doblin and van Sebille [28]. However, these two previous studies did not explicitly consider fitness and selection.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Equatorward-flowing currents, like the Falkland Current and Canary Current, have negative differential. These global patterns are also qualitatively similar to those for temperature offsets for drift of planktic foraminifera presented by van Sebille et al [26] and the inter-generational temperature ranges due to drift experienced by microbes presented by Doblin and van Sebille [28]. However, these two previous studies did not explicitly consider fitness and selection.…”
Section: Resultssupporting
confidence: 85%
“…The role of ocean currents on the temperature record incorporated into the shells of planktic foraminifera has been recognized and quantified using modeling [26, 27]. Over several generations, currents can move microbes across different temperature regions, which increases the range of temperatures they experience by up to 10°C, compared to the seasonal fluctuation at one location [28]. Therefore, the role of currents in ocean microbe biogeography is well-recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation between population structure and temperature is not entirely surprising. Temperature is an important factor regulating phytoplankton growth rates both between and within species, and likely plays a role in regulating dispersal capacity (51,52).…”
Section: Resultsmentioning
confidence: 99%
“…Microorganisms can travel long distances by hitchhiking on ocean currents, influencing microbial community assemblies (Brum et al., ; Doblin & van Sebille, ) from prokaryotes (Hamdan et al., ; Zhao et al., ) to microeukaryotes (Pernice et al., ). Previous studies have reported algae and plankton as intruders in the ECS through the KSWM (Dai et al., ; Hsieh et al., ).…”
Section: Discussionmentioning
confidence: 99%